2023
DOI: 10.1161/circimaging.123.015589
|View full text |Cite
|
Sign up to set email alerts
|

Remnant Cholesterol in Young Adulthood Is Associated With Left Ventricular Remodeling and Dysfunction in Middle Age: The CARDIA Study

Xinghao Xu,
Zhaoyan Wang,
Rihua Huang
et al.

Abstract: BACKGROUND: Recent studies have shown that remnant cholesterol (RC) is associated with incident heart failure; however, its association with left ventricular (LV) structure and function is unclear. We aimed to evaluate the association between RC levels in young adulthood and LV structure and function in middle age. METHODS: We included 3321 participants from the CARDIA study (Coronary Artery Risk Development in Young Adults) at baseline. RC was calculat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…There were studies indicating that residual cholesterol levels in adolescence were associated with left ventricular remodeling and dysfunction in middle age population. Even in a study of adolescents, it was demonstrated that elevated RC levels in young adulthood were linked to adverse left ventricular structural and functional abnormality in midlife 17 . All above studies showed a close relationship between remnant cholesterol and the development of cardiovascular diseases and highlighted the importance of monitoring and managing residual cholesterol levels to mitigate CVD risk.…”
Section: Discussionmentioning
confidence: 97%
“…There were studies indicating that residual cholesterol levels in adolescence were associated with left ventricular remodeling and dysfunction in middle age population. Even in a study of adolescents, it was demonstrated that elevated RC levels in young adulthood were linked to adverse left ventricular structural and functional abnormality in midlife 17 . All above studies showed a close relationship between remnant cholesterol and the development of cardiovascular diseases and highlighted the importance of monitoring and managing residual cholesterol levels to mitigate CVD risk.…”
Section: Discussionmentioning
confidence: 97%